Analiza związku elastyczności działania a efektywnością - Wiśniewski, Tomasz (Analysis of the Relationship Between Efficiency and Operation Flexibility, 2005)
The paper concentrate on ex ante efficiency analysis. The factor which extends the ex ante analysis is flexibility of operation. The influence of operational flexibility on efficiency is especially high when the planning horizon is long and the environment is highly volatile. The paper identifies the valuation methods which could be used for the valuation of operational flexibility.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 449-458